ANALISIS KEPUTUSAN PENGUNJUNG MEMBELI AYAM BETUTU PADA RUMAH MAKAN AYAM BETUTU KHAS GILIMANUK DI TUBAN BALI - Made Suardani (Politeknik Negeri Bali, 2013)
Bali is not just interesting for its culture but also the traditional dishes which have their own uniqueness. One of the most popular Balinesse dishes is ayam betutu or braissed chicken. The decision of visitors to choose the Ayam Betutu Khas Gilimanuk’s restaurant are influences by: (a) low price, (b) hot taste, (c) brand dolar as a restaurant’s identity, (d) packaging, (e) dish quality, (f) service, (g) the variety of the size. The perception of visitors and other related visitors about the strategy in developing of ayam betutu as a tourism culinary covering: (a) the visitor have known about it’s hot before buying, (b) all of the ingredients must be wash in order to keep its cleanliness before cooking, (c) the cheap price, (d) simple presenting, (e) the service is matched with the price (f) the professional staff (g) the parking area is not wide. The developing strategy can be done by : Strengths- Opportunities strategy by using the information technology as the information centre; Weakness-Opportunities strategy by promoting continuously; Strengths-Threat strategy by maintain the taste; and Weakness-Threat strategy by promoting with mass media such as TV and internet. In term of adaptation by adaptating in form, functions, ingredients, taste, ordertaking, presenting and the manner how to enjoy it.